2010
DOI: 10.4322/rbpv.01901002
|View full text |Cite
|
Sign up to set email alerts
|

Atividade inseticida in vitro do óleo de sementes de nim sobre Lutzomyia longipalpis (Diptera: Psychodidae)

Abstract: Lutzomyia longipalpis is the main vector of visceral leishmaniasis in Brazil. The objective was to evaluate the effect of oil from (Azadirachta indica) neem seeds on eggs, larvae and adults of the vector. The insects were captured in the field and kept in the laboratory at +/- 27 °C and 80% relative humidity. Five treatments with different concentrations were performed using two negative controls (distilled water and Tween 80) and a positive control. The eggs were sprayed with the oil at different concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is possible that the absence of plants with repellent or insecticidal qualities around homes can be a factor that maintains the presence of insects near the home when associated with the other environmental factors. According to a study, of insecticidal plants, oil from the seeds of Acalypha indica , popularly known as neem, has an insecticidal effect on the three stages of development of L. longipalpis , and this plant is easily grown in tropical regions [ 23 ]. An Ethiopian study of the neem plant concluded that the application of neem oil may be safe for personal use as a low-cost protective measure against sand fly bites for people living in endemic areas [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the absence of plants with repellent or insecticidal qualities around homes can be a factor that maintains the presence of insects near the home when associated with the other environmental factors. According to a study, of insecticidal plants, oil from the seeds of Acalypha indica , popularly known as neem, has an insecticidal effect on the three stages of development of L. longipalpis , and this plant is easily grown in tropical regions [ 23 ]. An Ethiopian study of the neem plant concluded that the application of neem oil may be safe for personal use as a low-cost protective measure against sand fly bites for people living in endemic areas [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…And according to Silva et al (2012) and Gomes et al (2016), cinnamon has antifungal and antibacterial activity and its main is compound eugenol, a substance with high antimicrobial power. Neem contains azadirachtin, considered a very important compound to which are attributed insecticide and antifungal actions, in synergy with other triterpenoids, geduinas, neembinm and limonoides (Maciel et al, 2010;Kasper et al, 2018).…”
Section: Assessment Of the Effect Of Different Plant Extracts On Fusa...mentioning
confidence: 99%
“…As substâncias naturalmente presentes nas plantas têm vantagem quando comparadas aos inseticidas sintéticos por serem recursos renováveis, serem rapidamente degradáveis e a seleção de indivíduos resistentes por parte dos mosquitos ser um processo mais lento, visto que as substâncias são compostas por associações complexas de princípios ativos (PROPHIRO et al, 2008) e não simplesmente por moléculas puras como os larvicidas sintéticos são. SOLTANI, 2009;DUA et al, 2009;MACIEL et al, 2010;PANT et al, 2012;VATANDOOST;VAZIRI, 2004). A moringa por sua vez contém o fitol como composto majoritário e apresentou o maior coeficiente de partição de todos (7,89) e CL50 superior a 1000 ppm (FERREIRA et al, 2009).…”
Section: Larvicidas Naturaisunclassified
“…Como alternativa, tem-se os larvicidas naturais, menos prejudiciais, geralmente provenientes de plantas, como no caso do neem (Azadirachta indica), tomilho (Thymus vulgaris) e jambu (Acmella oleracea). Os extratos e óleos essenciais dessas plantas apresentam diversas atividades biológicas, tais como: antimicrobiana, inseticida, larvicida e antioxidante (CRUZ et al, 2016;EL-AKHAL et al, 2016;FORIM et al, 2010;KADIR et al, 1989;KNIO et al, 2008;MACIEL et al, 2010;MARCOMINI et al, 2009;MESQUITA;SOUSA;INNECCO, 2010;MORDUE;NISBET, 2000;NICOLETTI et al, 2012;OLIVEIRA et al, 2016b;PANDEY et al, 2007;PAVELA, 2007;VRCHOTOVÁ;TŘÍSKA, 2009;PEREIRA et al, 2009aPEREIRA et al, , 2009bPRATES;VIANA;WAQUIL, 2003;ROMÃO et al, 2015;DIXIT, 2002;SHARMA et al, 2012;SIMAS et al, 2013;TRINDADE et al, 2000), as quais são associadas com a presença de metabólitos ativos: no caso do jambu, o espilantol; no caso do neem, a azadiractina; no caso do tomilho, o timol.…”
Section: Introductionunclassified
See 1 more Smart Citation